National Culture, IFRS Convergence, and The Accounting Quality: Evidence from EAGLEs Countries - Anisah Novi Karunia; Atika NurFauzia; Nur Zahra Yulitaningtias (The Indonesian Journal of Accounting Research, 2020)
This study aims to evaluate the influence of national culture on the relationship between IFRS convergence and accounting quality of companies in Emerging and Growth Leading Economies (EAGLEs) countries. This study uses measurements of accounting quality: earnings management, timely loss recognition, and value relevance. Cultural factors are measured using Gray's (1988) measurements. The sample in this study were 14 countries with a total of 6,832 observations in the 2012-2018 period. The data in this study used secondary data obtained from the Osiris Database. The results of this study provide evidence that accounting quality in EAGLE countries is positively related to the level of IFRS convergence, especially in earnings management and timely recognition of losses. This shows that IFRS convergence can reduce earnings management and improve the timely recognition of losses. Other results in this study, cultural factors, especially on the value of conservatism, partially support the relationship of IFRS convergence and accounting quality, while the value of secrecy is not support. Keywords: IFRS convergence, accounting quality, national culture, accounting standards, EAGLEs countries